Preferential phosphatidylglycerol synthesis via phosphorus supply through rRNA degradation in the cyanobacterium, Synechocystis sp. PCC 6803, under phosphate-starved conditions - Hiyoshi, Tatsunori; Haga, Megumi; Sato, Norihiro (Frontiers in Plant Science, 2024)
Photosynthetic organisms often encounter phosphorus (P) limitation in natural habitats. When faced with P limitation, seed plants degrade nucleic acids and extraplastid phospholipids to remobilize P, thereby enhancing their internal-P utilization efficiency. Although prokaryotic and eukaryotic photosynthetic organisms decrease the content of phosphatidylglycerol (PG) under P-limited conditions, it remains unclear whether PG is degraded for P remobilization. Moreover, information is limited on internal-P remobilization in photosynthetic microbes. This study investigates internal-P remobilization under P-starvation (-P) conditions in a cyanobacterium, Synechocystis sp. PCC 6803, focusing on PG and nucleic acids. Our results reveal that the PG content increases by more than double in the -P culture, indicating preferential PG synthesis among cellular P compounds. Simultaneously, the faster increases of glycolipids counteracted this PG increase, which decreases the PG proportion in total lipids. Two genes, glpD and plsX, contribute to the synthesis of diacylglycerol moieties in glycerolipids, with glpD also responsible for the polar head group synthesis in PG. The mRNA levels of both glpD and plsX are upregulated during -P, which would cause the preferential metabolic flow of their P-containing substrates toward glycerolipid synthesis, particularly PG synthesis. Meanwhile, we find that RNA accounts for 62% of cellular P, and that rRNA species, which makes up the majority of RNA, are degraded under -P conditions to less than 30% of their initial levels. These findings emphasize the importance of PG in -P-acclimating cell growth and the role of rRNA as a significant internal-P source for P remobilization, including preferential PG synthesis.